GENERAL MODEL OF THE ELECTRONIC INFORMATION ENVIRONMENT, BASED ON THE MIRRORS CONCEPT - Kovalenko, Olena (Scientific Works of Vinnytsia National Technical University, 2019)
The paper considers the mirror concept for the construction of the model of the information environment in order to determine the general composition and functional units of the electronic information environment. The results of the recent studies analysis regarding the solution of the problems, dealing with the formation of the sufficiently optimal electronic information environment, adapted to the specific situation, problem and even tastes of the users prove that its target purpose is not always focused on the main tasks of the situational directions of the user’s activity. The needs of the users of electronic information environment are the following information space and its situational operation field must be constructed with the possibility of easy determination of the actions at any moment, assessment of the current state of the system, accessible monitoring of the results. On the base of the theories of the information environment, organization, information systems the definition of the electronic information environment is specified as the set of the hardware and software resources, formed in a single electronic information environment for obtaining the set goals by means of realization of the determined algorithms of the activity processes automation, communication realization, data and knowledge processing with further formation of electronic resources. General model of the electronic information environment is suggested, this model represents the connected set of the models of electronic information space, containing such components (mirrors) as: mirror of the current state of the activity – system of monitoring and control; mirror of the planned (ideal) state of the activity, which is formed as the example of the indices system, description of the technological and control processes, forecast calculations for the innovation projects; decision-making risks, etc; mirrors of variational realizations, depending on the state and possibilities of the external and internal environment. Besides, the strategic mirror of the operation and development indices of the organization and/orthe project shows the correspondence of the current (or forecast indices) to the strategic indices. Functional mirror of the activity processes (including automation processes) – availability of the working field of execution or/and reporting regarding technological and managerial processes. Motivation mirror of the activity processes contains the results of the best projects and the description of the best practices, indices for the comparison etc. The suggested model is also presented mathematically. Testing of the concept and the model is performed on the example of the formation of the electronic information environment of the enterprise and university.